Feasibility of dry cooling in supercritical CO2 power cycle in concentrated solar power application: Review and a case study. (October 2020) - Ehsan, M. Monjurul; Guan, Zhiqiang; Gurgenci, Hal; Klimenko, Alexander
Abstract: Past research intensely stressed the application of supercritical CO2 (sCO2 ) in power cycles for large-scale electricity generation in the near future by adapting decarbonization policy with clean energy technologies. The prominent closed-loop sCO2 Brayton cycle has all the potential for the future power generation over the traditional superheated/supercritical Rankine cycle for concentrated solar power applications. Using sCO2 as a working fluid has been preferred as one of the most efficient and environmentally safe alternatives over the traditional refrigerants and other working fluids. While the thermodynamic analysis of sCO2 cycles has been in a great number of recent studies, its particular advantages when coupled with dry cooling have not been adequately analyzed. The sCO2 power cycle efficiency is highly influenced by the cycle lowest temperature, hence cooling system design significantly impacts the cycle performance. In the present work, the applicability and the potential benefits of the dry cooling system are demonstrated for sCO2 cycles over the traditional Rankine cycle. The detailed thermodynamic modelling of the dry cooling system is presented. Research studies on dry cooled sCO2 power cycles are reviewed with their major findings. Various techniques are identified from the literature to compensate for the efficiency degradation of the power cycle during high ambient temperature. The implementation of the extremum seeking controller, the hybrid cooling, and the radiative cooling option certainly can improve the cycle performance at the off-design condition. A thermodynamic analysis is performed to design the cooling tower for recompression and the partial cooling cycles. The nodal approach adapted in the present work allows predicting the radical variation of transport properties inside the tubes of the heat exchanger. The towers are designed based on the optimum operating condition of the power cycle. The cycle performance is investigated with the variation sCO2 entrance temperature into the cooling system and the ambient temperature. This case study shows a pathway in designing the cooling system for sCO2 power cycles. This review work highly emphasizes the potential benefits of dry cooling in sCO2 power cycles and presents the cooling system design methodology for efficient cycle operation. Highlights: Potential benefits of dry cooling in sCO2 power cycle compared to steam cycle. Detailed design methodology of the dry cooling system is presented. Review of literature on dry cooled sCO2 power cycles and current research status. Identification of various cooling options to address performance degradation. Designing the cooling system for two sCO2 power blocks.